Macrophage elastase derived from adventitial macrophages modulates aortic remodeling - Chen, Yajie; Yang, Xiawen; Kitajima, Shuji; Quan, Longquan; Wang, Yao; Zhu, Maobi; Liu, Enqi; Lai, Liangxue; Yan, Haizhao; Fan, Jianglin (Frontiers in Cell and Developmental Biology, 2023)
Abdominal aortic aneurysm (AAA) is pathologically characterized by intimal atherosclerosis, disruption and attenuation of the elastic media, and adventitial inflammatory infiltrates. Although all these pathological events are possibly involved in the pathogenesis of AAA, the functional roles contributed by adventitial inflammatory macrophages have not been fully documented. Recent studies have revealed that increased expression of matrix metalloproteinase-12 (MMP-12) derived from macrophages may be particularly important in the pathogenesis of both atherosclerosis and AAA. In the current study, we developed a carrageenan-induced abdominal aortic adventitial inflammatory model in hypercholesterolemic rabbits and evaluated the effect of adventitial macrophage accumulation on the aortic remodeling with special reference to the influence of increased expression of MMP-12. To accomplish this, we compared the carrageenan-induced aortic lesions of transgenic (Tg) rabbits that expressed high levels of MMP-12 in the macrophage lineage to those of non-Tg rabbits. We found that the aortic medial and adventitial lesions of Tg rabbits were greater in degree than those of non-Tg rabbits, with the increased infiltration of macrophages and prominent destruction of elastic lamellae accompanied by the frequent appearance of dilated lesions, while the intimal lesions were slightly increased. Enhanced aortic lesions in Tg rabbits were focally associated with increased dilation of the aortic lumens. RT-PCR and Western blotting revealed high levels of MMP-12 in the lesions of Tg rabbits that were accompanied by elevated levels of MMP-2 and -3, which was caused by increased number of macrophages. Our results suggest that adventitial inflammation constitutes a major stimulus to aortic remodeling and increased expression of MMP-12 secreted from adventitial macrophages plays an important role in the pathogenesis of vascular diseases such as AAA.